The Role of Good Corporate Governance in Moderating the Effect of Financial Ratio on Financial Distress (Study of Consumer Sector Companies Listed on the Indonesia Stock Exchange Over Period 2018-2020) - Riesta, Gabriella Ika; Septriana, Ira (Universitas Dian Nuswantoro Semarang, 2023)
Financial distress is a condition where management fails to manage company finances. This study aims to determine the effect of leverage, net profit margin, liquidity, and sales growth on financial distress with corporate governance as a moderating variable. This sample used all consumer goods sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Sampling was used with the purposive sampling technique and selected 25 companies. Data analysis used multiple linear regression and the absolute difference value test. The results are that the variables of leverage, net profit margin, and liquidity affect predicting financial distress. Meanwhile, sales growth does not affect financial distress. As measured by managerial ownership, corporate governance can moderate the effect of liquidity on financial distress. Still, it cannot moderate the effect of leverage, net profit margin, and sales growth on financial distress. Keywords:leverage, net profit margin, liqudity, sales growth, financial distress, good corporate governance